Social Network and Local Interest as the Strength of Local Television - Maryani, Eni; Mulyana, Deddy; Karlina, Siti; Rosfiantika, Evi; Rahmawan, Detta (International Journal of Psychosocial Rehabilitation, 2019)
This study aims to understand the phenomenon of local media, especially television, which experiences various obstacles in its development. In Indonesia, many local televisions in the various region originally owned by local entrepreneurs turned into networked media owned by national entrepreneurs. Therefore this study specifically aims to look at the strength of local stations and how implications of local station changes become a network station. Through case studies on local television in Palembang and Bandung, and data collection techniques of in-depth interviews and focus group discussions (FGD), this study gathered a variety of data from the Indonesian Local Televisions Association (ATVLI), Indonesian Broadcasting Commission (KPI), Media Law Experts, Local Television Practitioners, and Media Observers. Based on the results of this study, local television struggles to survive because it cannot compete with national television networks. Local television could develop and sustain through the strength of social networks and local concerns/interests from their audiences. Through these two factors, local television could develop local content that has relevance to local audiences and elevates local identity in its content. However, to develop local content as a form of content diversity in a democratic media system, a clear policy related to media ownership is needed to provide space for local media practitioners to develop local content in each of their respective media